2019
DOI: 10.1021/acs.molpharmaceut.8b01143
|View full text |Cite
|
Sign up to set email alerts
|

Development of Simplified in Vitro P-Glycoprotein Substrate Assay and in Silico Prediction Models To Evaluate Transport Potential of P-Glycoprotein

Abstract: For efficient drug discovery and screening, it is necessary to simplify P-glycoprotein (P-gp) substrate assays and to provide in silico models that predict the transport potential of P-gp. In this study, we developed a simplified in vitro screening method to evaluate P-gp substrates by unidirectional membrane transport in P-gp-overexpressing cells. The unidirectional flux ratio positively correlated with parameters of the conventional bidirectional P-gp substrate assay (R 2 = 0.941) and in vivo K p,brain ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…This difference is more pronounced for poorly permeable compounds, as they are more greatly affected by the active contribution of P-gp (equations 10 and 13). Although uni-directional measurements similar to AP-ER have been described previously (Thiel-Demby et al, 2004;Ohashi et al, 2019) and are able to differentiate strong and weak P-gp substrates, these studies also showed correlation between estimates based on uni-directional measurements and classical ER, and hence superiority of uni-directional measurements over bi-directional models was not described.…”
Section: Conceptual Difference Between the Uni-directional Ap-er And mentioning
confidence: 79%
“…This difference is more pronounced for poorly permeable compounds, as they are more greatly affected by the active contribution of P-gp (equations 10 and 13). Although uni-directional measurements similar to AP-ER have been described previously (Thiel-Demby et al, 2004;Ohashi et al, 2019) and are able to differentiate strong and weak P-gp substrates, these studies also showed correlation between estimates based on uni-directional measurements and classical ER, and hence superiority of uni-directional measurements over bi-directional models was not described.…”
Section: Conceptual Difference Between the Uni-directional Ap-er And mentioning
confidence: 79%
“…It was previously reported that PCA could show the distribution of chemical space in the dataset. 21 Components 1, 2, and 3 explained 62.3, 12.0, and 8.0% of the variance, respectively. Figure 1 shows that the compounds were effectively separated into the training and test datasets.…”
Section: Resultsmentioning
confidence: 99%
“…The compounds were separated into the training and test sets for the construction and subsequent verification of the prediction models. To ensure unbiased segregation, the PCA analysis was conducted based on 11 representative molecular descriptors, which are generally considered important for synthetic expansion [19,20]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…of 2:1. To investigate applicability domain, 11 molecular parameters were used as reported previously [19] with JMP Pro PCA (Principal component analysis) [19].…”
Section: Separation Of Compounds Into Training and Test Sets And Theimentioning
confidence: 99%